Determining the optimal technique for early detection of broken rotor bars in medium voltage squirrel cage induction motors during operation - Thusi, Lourenco Mafika (My University, 2010)
Electric motors play a pivotal role in various industrial plant processes for electrical to mechanical energy conversion. As a result their reliability and availability is of utmost importance to industries. The reliability and availability of plant electric motors can be achieved by early detection of any developing fault by performing condition monitoring and preventative maintenance on motors. An important motor failure mode, which has been quite challenging to detect, is cracking and subsequent breaking of rotor bars in induction motors. The existing condition monitoring techniques are incapable of positively detecting a cracked or single bar problem during operating conditions. Bars have broken, lifting out of the rotor slots and damaging all stator coils, consequently forcing the removal of the motor during plant operation and a complete rewind of the stator. This research is being conducted to ascertain, from existing conventional techniques, an optimal technique for the detection of a cracked rotor bar or a completely broken single rotor bar in induction motors under operating conditions. Furthermore, it explores non-conventional techniques, which can assist in detection of broken rotor bars. The report starts by presenting the literature on stator current and axial vibration analysis which are conventional rotor bat detection techniques. Thereafter, the Maxwell 2D simulation results which indicate stator current broken rotor bar detection frequencies are discussed, followed by the experimental measurement results and discussions. The conclusion drawn from the experimental results is that the stator current analysis is, presently, the optimal technique to detect a single broken rotor bar during a medium voltage induction motor operation. The axial vibration analysis is recommended as a secondary monitoring technique to solidify the stator current diagnosis. The shaft voltage analysis is introduced as a non-conventional technique and the shaft voltage results are discussed.